Validation of the Moral Injury Outcome Scale in acute care nurses - Tao, Hong; Nieuwsma, Jason A.; Meador, Keith G.; Harris, Stephanie L.; Robinson, Patricia S. (Frontiers in Psychiatry, 2023)
Introduction Moral injury, predominantly studied in military populations, has garnered increased attention in the healthcare setting, in large part due to the psychological and emotional consequences of the COVID-19 pandemic. The measurement of moral injury with instrumentation adapted from military settings and validated in frontline healthcare personnel is essential to assess prevalence and guide intervention. This study aimed to validate the Moral Injury Outcome Scale (MIOS) in the population of acute care.Methods A sample of 309 acute care nurses completed surveys regarding moral injury, depression, anxiety, burnout, professional fulfillment, spiritual well-being, and post-traumatic stress disorder symptoms. Confirmatory factor analysis was conducted as well as an assessment of reliability and validity.The internal consistency of the 14-item MIOS was .89. The scale demonstrated significant convergent and discriminant validity and test of construct validity confirmed the twofactor structure of shame and trust violation in this clinical population. Regression analysis indicated age, race, and marital status-related differences in the experience of moral injury.The MIOS is valid and reliable in acute care nursing populations and demonstrates sound psychometric properties. Scores among nurses diverge from those in military personnel in areas that may inform distinctions in interventions to address moral injury in these populations.